Income redistribution policies in a Schumpeterian economy - Leal, Guilherme Strifezzi (2017)
We study the effects of redistributive taxation on growth, inequality and welfare in a Schumpeterian economy and compare the outcomes of different policies. The model features a structure of vertical innovations based on the concept of creative destruction and contains risk-averse agents and elastic labor supply. Contrary to previous findings, we show that excessive tax rates discourage research effort, but moderate redistribution can stimulate it. We analyze the results for three different policies: equal redistribution to all agents, research subsidy and innovation bonus. While the first is better in terms of reducing inequality, the others are more efficient to promote research effort and economic growth. We show that the best policy in terms of welfare generation changes as we increase the amount of skilled individuals in the economy, and that the obtained outcomes do not support the hypothesis of convergence.